Virtual reality simulator training – a new era in surgical education program / Učenje s simulatorji – novo obdobje v izobraževanju kirurgov - Pahor, Dušica (Acta Medico-Biotechnica, 2021)
With the opening of a new building of the Faculty of Medicine, University of Maribor in September 2013 with all the modern simulator equipment for surgical teaching a completely new opportunity was achieved, including several novel aspects of surgical simulation in resident education.